Abnormal implies WNSCC

From Groupprops
Jump to: navigation, search
This article gives the statement and possibly, proof, of an implication relation between two subgroup properties. That is, it states that every subgroup satisfying the first subgroup property (i.e., abnormal subgroup) must also satisfy the second subgroup property (i.e., WNSCC-subgroup)
View all subgroup property implications | View all subgroup property non-implications
Get more facts about abnormal subgroup|Get more facts about WNSCC-subgroup

Statement

Statement with symbols

Suppose H is an abnormal subgroup of a group G. Then, H is a WNSCC-subgroup of G: for any two normal subsets A,B of H with gAg^{-1} = B for some g \in G, we have A = B.

Definitions used

(These definitions use the left action convention, but using the right action convention does not change any of the proofs).

Abnormal subgroup

Further information: Abnormal subgroup

A subgroup H of a group G is termed abnormal in G if, for any g \in G, we have g \in \langle H, gHg^{-1} \rangle.

WNSCC-subgroup

Further information: WNSCC-subgroup

A subgroup H of a group G is termed WNSCC in G if, for any two normal subsets A,B of H such that there exists g \in G with gAg^{-1} = B, we have A = B.

Related facts

Stronger facts

Proof

Given: A group G, an abnormal subgroup H. Two normal subsets A,B of H such that there exists g \in G with gAg^{-1} = B.

To prove: A = B.

Proof:

  1. H \le N_G(A) and H \le N_G(B) (here N_G(B) denotes the normalizer of the subset B in G): This is a direct consequence of the fact that A, B are normal subsets of H.
  2. gHg^{-1} \le N_G(B): Since H \le N_G(A), and conjugation by g is an automorphism, we get gHg^{-1} \le N_G(gAg^{-1}), yielding gHg^{-1} \le B.
  3. \langle H, gHg^{-1} \in N_G(B): This follows from the previous two steps.
  4. g \in N_G(B): Since H is abnormal, g \in \langle H, gHg^{-1}. Combining this with the previous step yields g \in N_G(B).
  5. A = B: Since g \in N_G(B), we have g^{-1} \in N_G(B), so g^{-1}Bg = B. Also, by assumption, g^{-1}Bg = A. Combining these, we get A = B.